Evaluation of Aggregate Stability and Geotechnical Properties of Soils Derived from Dissimilar Shaley Lithological Materials in Selected Locations of Southeastern Nigeria - Ahukaemere, C. M.; Obasi, S. N.; Agim, L. C.; Egwuonwu, K. K. (Scientific Modelling and Research, 2020)
This research was carried out under three major dissimilar shaley lithological parent materials in selected locations of Southeastern Nigeria. The soil aggregate stability and geotechnical properties were major objects of investigations. Pedons were dug; one in each location of Imo clay shale in Okigwe, Bende-Ameki shale in Uzuakoli and Asata Nkporo shale in Amaike Izzi, all located in Imo, Abia and Ebonyi States of Southeastern Nigeria respectively. These areas lie between Latitude 5o 45’ 48" N and Longitude 7o 14’ 37" E, Latitude 5o 45’ 48" N and Longitude 7o 14’ 37" E, Latitude 5o 55’ 49" and Longitude 7o 58’ 31" E for Okigwe, Uzuakoli and Amaike Izzi respectively. Soil aggregate stability and geotechnical properties were studied from the pedons. From the results, Imo clay shale had the highest average clay fraction (316.5 g kg-1). The mean sand content ranged from 620 - 690.5 g kg-1 and differed significantly (p = 0.05) across the parent materials. The organic Carbon content of the soil varied significantly with means ranging from 8.68 - 14.73 g kg-1. Results of the aggregate stability showed that the Clay flocculation index (CFI) and Clay dispersion ratio (CDI) ranged from 23.10 - 37.59 and 62.2 - 76.27 respectively and tend to have a negative relationship with each other. However, the CFI and CDI of the soils did not differ significantly. The water stable aggregate (WSA) and mean weight diameter (MWD) also did not vary significantly and ranged from 84.25 - 97.20 and 1.59 - 1.72 respectively. The result of the geotechnical properties showed that liquid limit, plastic limit and plasticity index varied significantly with the means ranging from 0.00 - 48.85, 0.00 - 21.68 and 0.00 - 27.18 respectively.